Comparative Analysis of Pedagogical Strategies Across Disciplines in Open Distance Learning at Unisa - Ramdass, Kemlall; Masithulela, Fulufhelo James (International Review of Research in Open and Distributed Learning, 2016)
Re-engineering technological strategies in teaching and learning in an open distance learning (ODL) environment is paramount as the demand for access to quality higher education escalates drastically on a year to year basis. The organisational framework requires change in order to accommodate the increasing number of students. In view of the changing higher education landscape and the increase in the number of students qualifying for higher education acceptance, open distance education has been opened to residential institutions. Despite the fact that demands is greater than supply in the higher education sector, the University of South Africa (Unisa), in reaction to the “competitive threat,” has embarked on the re-evaluation of ODL as a component of its teaching and learning methodology. Unisa focussed on its pedagogical approaches as a primary means of maintaining its competitive edge. The challenges in the higher education sector are also attributed to the basic education sector that does not prepare students sufficiently for higher education. ODL, if applied appropriately, could be a strategy to address the issues of access, equality, and equity in a democratic South Africa. Pedagogical strategies that are functional and appropriate need to be applied in the higher education sector. Hence the research question is to determine what ODL strategies can be implemented to ensure that students are on par with traditional universities. Therefore, this paper explores the pedagogical strategies that colleges may use with the intent to improve delivery of teaching and learning in an ODL environment.